Association of GDF15 With Inflammation and Physical Function During Aging and Recovery After Acute Hospitalization: A Longitudinal Study of Older Patients and Age-Matched Controls. (11th January 2021) - Tavenier, Juliette; Rasmussen, Line Jee Hartmann; Andersen, Aino Leegaard; Houlind, Morten Baltzer; Langkilde, Anne; Andersen, Ove; Petersen, Janne; Nehlin, Jan O
Abstract: Growth differentiation factor 15 (GDF15) is a stress-induced cytokine. Its plasma levels increase during aging and acute illness. In older Patients and age-matched Controls, we evaluated whether GDF15 levels (i) were associated with recovery after acute illness, and (ii) reflected different trajectories of aging and longitudinal changes in health measures. Fifty-two older Patients (≥65 years) were included upon admission to the emergency department (ED). At 30 days after discharge (time of matching), Patients were matched 1:1 on age and sex with Controls who had not been hospitalized within 2 years of inclusion. Both groups were followed up after 1 year. We assessed plasma levels of GDF15 and inflammatory biomarkers, frailty, nutritional status (mini nutritional assessment short-form), physical and cognitive function, and metabolic biomarkers. In Patients, elevated GDF15 levels at ED admission were associated with poorer resolution of inflammation (soluble urokinase plasminogen activator receptor [suPAR]), slowing of gait speed, and declining nutritional status between admission and 30-day follow-up. At time of matching, Patients were frailer and overall less healthy than age-matched Controls. GDF15 levels were significantly associated with participant group, on average Patients had almost 60% higher GDF15 than age-matched Controls, and this difference was partly mediated by reduced physical function. Increases in GDF15 levels between time of matching and 1-year follow-up were associated with increases in levels of interleukin-6 in Patients, and tumor necrosis factor-α and suPAR in age-matched Controls. In older adults, elevated GDF15 levels were associated with signs of accelerated aging and with poorer recovery after acute illness.